Functional characterization of the nuclear localisation and export signals of the human Hsp70/Hsp90 organising protein (HOP) - Rousseau, Robert P (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2019)
Expected release date-April 2021
Keywords: Uncatalogued